Combined Factors for Predicting Cognitive Impairment in Elderly Population Aged 75 Years and Older: From a Behavioral Perspective - Yan, Zhixiong; Zou, Xia; Hou, Xiaohui (Frontiers in Psychology, 2020)
To unravel the combined effect of risk and protective factors that may contribute to preserve or impair cognitive status, this prospective cohort study systematically investigated a cluster of factors in elders aged 75 years and older from Guangxi Longitudinal Cohort (GLC) dataset. GLC has tracked 630 oldest-elders for 2 times within 2 years and will continue to follow 2 times in next 4 years. At baseline geriatric assessment, sociodemographic information (e.g., education, Mandarin, marriage, income), physical status (BMI, chronic disease/medicine), lifestyle factors (smoking, alcohol, exercise), and self-rated mental health (selfcare, wellbeing, anxiety) were recorded by online interview. With 2 years follow-up, Mini-Mental State Examination (MMSE) and memory test were performed through person-to-person interview. The performance of MMSE was applied to represent responder’s cognitive status which classified into cognitive impairment and normal group based on cut-off point 20. An age-related cognitive declining trend of fifteen stratified factors were observed, though with small effect size (R-square:0.001-0.15). the odds of exposure or non-exposure on factors (Memory, selfcare, exercise, income, education and literate) had significantly different effect on cognitive impairment through multivariate analysis after adjusted other confounding variables. Through stepwise multiple logistic regression analysis, the following 12 factors/index would be integrated to predict cognitive impairment: gender, physical health factors (BMI, chronic disease), socioeconomic and lifestyle factors (education, literate, mandarin, marriage, income, and exercise), and psychological health factors (memory, selfcare cognition, and anxiety). Related clinical and nursing application were discussed.